2015
DOI: 10.1007/s40812-015-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Contract and procurement design for PPPs in highways: the road ahead

Abstract: We review international practice in concession-based public private partnerships (PPPs) for highways, in the light of the economic theory of incentives, procurement and regulation. In particular, we analyse alternative funding mechanisms to cover highway costs, and their impact on demand risk allocation, incentives, cost of capital, and likelihood of renegotiation. We note how real tolls must pursue a number of contrasting objectives, which may be best served by introducing tariff discrimination. We discuss al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Before 2001, national legislation introduced a general rule providing for automatic, yearly price adjustments based on inflation, a widely employed regulation in this industry (Iossa, 2015).…”
Section: Insert Table 5: Spearman Rank-order Correlations Of Cost Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Before 2001, national legislation introduced a general rule providing for automatic, yearly price adjustments based on inflation, a widely employed regulation in this industry (Iossa, 2015).…”
Section: Insert Table 5: Spearman Rank-order Correlations Of Cost Efficiencymentioning
confidence: 99%
“…These Public-Private Partnership (PPP) contracts are designed and awarded in the expectation of improving efficiency and, above all, of facilitating private financing. However, toll regulation has typically been shown to be unrelated to the degree of productivity or the efficiency of concessionaires (Albalate, Bel and Fageda, 2009), especially in the absence of price-cap regulation (Iossa, 2015), and satisfying uncertain demand in the long run is the main factor determining the outcome of the standard fixed-term concession contract (Engel, Fischer and Galetovic, 1997a;2001). 2 Even if motorway managers appear to 1 See Matas, Raymond and Roig (2015) for recent studies on the link between road investments and productivity;…”
Section: Introductionmentioning
confidence: 99%
“…Iyer and Sagheer (2012) found that the grant sought from the government is the sole bidding variable for Indian buildoperate-transfer (BOT) highway projects. Iossa (2015) summarized that the key variables in PPP procurement generally include toll, shadow tolls, net present value, concession period, risk allocation and revenue share. In China, hosting governments are in charge of designing the initial concession agreement.…”
Section: Balance Public and Private Interests Through Concession Agrementioning
confidence: 99%
“…In a PPP project, a private party or consortium is granted a concession to finance, build, and operate a public project and to provide the corresponding product or service and collect ensuing revenues (Xiong and Zhang 2014). The PPP approach may increase the economic value of infrastructure outputs because management by a private entity can bring important efficiency gains to the public authority body in question (Liu et al 2014;Iossa 2015). However, in the case of unexpected events, a project can suffer high-profile failures.…”
Section: Introductionmentioning
confidence: 99%